5.5 AGE-DEPENDENT TELOMERE ATTRITION, SHORT TELOMERES AND ATHEROSCLEROSIS - Simon Toupance; Anna Kearney-Schwartz; Mohamed Temmar; Cécile Lakomy; Carlos Labat; Patrick Rossignol; Faiez Zannad; Patrick Lacolley; Abraham Aviv; Athanase Benetos (Artery Research, 2016)
Background: Short leukocyte telomere length (LTL) is associated with atherosclerosis. The prevailing view is this association exists since LTL is a biomarker of cumulative inflammation and oxidative stress during adult life. However recent studies show that LTL in adults is defined mainly by LTL at birth and attrition during childhood. Therefore we can suggest that short LTL might precede clinical expression of atherosclerosis. Objectives: To examine the directionality in the relation between carotid atheroma and LTL dynamics. Methods: LTL was measured by TRF in samples donated 9 years apart on average by 257 men and women aged 41 to 80 at the inclusion. Results: LTL attrition during follow-up (FU) period was 25±17 bp/year. No relation was observed between LTL attrition and presence of carotid atherosclerotic plaques (PCAP). Baseline (BL)-LTL was highly correlated (r=0.96, p<0.0001) with FU-LTL. In 87.9%of the subjects LTL ranking by deciles was the same 1 decile at BL and FU. BL- and FU-LTL were inversely associated with PCAP (p<0.01). After adjusting for age and gender, BL-LTL was 6.50±0.04 Kb in subjects without PCAP 6.46±0.06 in those with PCAP only at the FU visit and 6.27±0.06 in those with PCAP in both BL and FU visits (p=0.027). LTL attrition was the same in these groups. Conclusions: LTL attrition in adulthood is not influenced by PCAP and does not play a significant role in LTL ranking. By contrast, patients with shorter telomeres present CAP earlier in life. Telomere length could be considered as a bio-determinant for atherosclerosis.